Enhancement DPT Method in Terms of Estimation Chirp Rate and Central Frequency Parameters of the LFM Signal - Rabiee, Nooshin; Azad, Hamid; Parhizgar, Naser (Společnost pro radioelektronické inženýrství, 2019)
The discrete polynomial-phase transform (DPT) method estimate chirp rate and central frequency of LFM signal based on sequential estimation of polynomial phase parameters. This method uses Nonlinear Least Squares (NLS) technique (based on FFT) to estimate phase parameters of the LFM signal. Although NLS enjoys a high level of statistical accuracy, it entails a lot of calculations. In this paper, in order to enhance the precision of estimation and also to reduce the calculations in DPT method, a technique called "combined" is proposed and used in DPT method in order to estimate chirp rate and central frequency of LFM signal .The combined technique firstly provides an initial estimate of frequency interval based on NLS criterion in single-exponential mode, then using initial estimation and Random Basis Functions method (RBF). Simulation results are presented to demonstrate better performance of DPT method by combined technique in order to estimate phase parameters of LFM signal as compared with the existing techniques.
Keywords: Discrete Polynomial Phase Transform (DPT); Nonlinear Least Square (NLS); Synthetic Aperture Radar (SAR); Linear Frequency Modulation (LFM)